The Effectiveness of Using E-Learning as Learning Media During the Covid Pandemic 19 - Lilis Ardini; Ulfah Setia Iswara; Endang Dwi Retnani (Universitas Medan Area, 2020)
The research objective is to provide an assessment of the effectiveness of the use of e-learning methods during the Covid 19 pandemic. Learning methods using e-learning began to be used when the corona virus outbreak became a global pandemic. This research is a descriptive study with a quantitative approach. The research was conducted on 275 accounting students of the Diploma and Undergraduate Program of STIESIA Surabaya who carried out learning activities through e-learning. E-learning in the STIESIA Surabaya environment uses the address https://elearning.stiesia.ac.id. The online questionnaire was filled out by students via Google Form in the month of June and then processed and analyzed the data. There are 20 indicators as an assessment of effectiveness of learning. The results showed that e-learning was considered by students to be quite effective as a learning method. There are still many obstacles faced by students when doing online learning using e-learning. However, along with the development of information technology, e-learning is expected to improve understanding of learning materials and make learning more efficient